2021
DOI: 10.3748/wjg.v27.i22.3064
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and pediatric fatty liver disease: Is there interplay?

Abstract: The rapid global spread of coronavirus disease 2019 (COVID-19) infection has become a major health issue with higher morbidity and mortality rates. Besides respiratory symptoms, a growing body of evidence indicates a variety of gastrointestinal manifestations including liver involvement. In this regard, several data supported an association between COVID-19 infection and liver injury in adults, while in children there is compelling but currently limited evidence. In particular, patients with COVID-19 have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…28 Previous studies found increased liver enzymes in 25% of children with COVID-19, which reached 50% in severe and critically ill individuals. 29 Omran et al 30 reported that elevated liver enzymes are predictors of the severity of COVID-19. In the current study, ALT and AST had a positive correlation with Hcy levels, which is consistent with the findings of Lv et al 31 Although Hcy levels rise in patients with renal failure, we could not detect a link between Hcy and serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Previous studies found increased liver enzymes in 25% of children with COVID-19, which reached 50% in severe and critically ill individuals. 29 Omran et al 30 reported that elevated liver enzymes are predictors of the severity of COVID-19. In the current study, ALT and AST had a positive correlation with Hcy levels, which is consistent with the findings of Lv et al 31 Although Hcy levels rise in patients with renal failure, we could not detect a link between Hcy and serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 liver injury could be caused by direct viral invasion via angiotensin‐converting enzyme 2 receptors in the liver, or it could be immune‐mediated or drug‐induced 28 . Previous studies found increased liver enzymes in 25% of children with COVID‐19, which reached 50% in severe and critically ill individuals 29 . Omran et al 30 reported that elevated liver enzymes are predictors of the severity of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Although most infected individuals are asymptomatic, the typical COVID-19 disease presents as mild to severe progressive pneumonia. SARS-CoV-2 infection can affect all the systems of the human body, and emerging data suggest that COVID-19 has pulmonary and extrapulmonary manifestations including hepatic injury subsequently progressing to multiorgan damage and death particularly in elderly patients ( Di Sessa et al, 2021 ).…”
Section: Xenophagy and Virophagy: Selective Autophagic Elimination Of...mentioning
confidence: 99%
“…Metabolic-associated fatty liver disease (MAFLD) patients have a higher risk of SARS-CoV-2 infection and increased liver dysfunction in comparison to patients without MAFLD. Dysregulated hepatic immunity in NAFLD patients can participate in COVID-19 pathogenesis because immune cells (e.g., Kupffer cells) can produce active cytokines and aggravate or contribute to the cytokine storm ( Di Sessa et al, 2021 ).…”
Section: Roles Of Mitophagy and Lipophagy In Hepatic Physiology And P...mentioning
confidence: 99%
See 1 more Smart Citation